Gut Bacterial Community of the Lone Star Tick (Amblyomma americanum) - Fergurson, Anna; Maldonado-Ruiz, Paulina; Zurek, Ludek (My University, 2017)
Ticks are obligate blood feeding ectoparasites and vectors of several animal and human pathogens (Williams-Newkirk et al., 2014). Ticks not only carry pathogens but also a bacterial community with commensal and symbiotic relationships (Bonnet et al., 2017). In other arthropod vectors, the gut microbiome influences their competence for pathogens they transmit. In this study, we used a culturing approach to assess the prevalence, abundance, and diversity of bacteria in the gut of adult lone start ticks (Amblyomma americanum) (n = 31) collected in Kansas. We were unable to culture any bacteria from 42% of ticks and the mean bacterial concentration was only 11.8 ± 5.4 CFU/tick. Amplification and sequencing of 16S rDNA of bacterial isolates (n= 36) revealed a low bacterial diversity represented by 3 phyla: Actinobacteria (50%), Firmicutes (40%), Proteobacteria (10%) and 16 genera with a heavy bias toward Grampositive and catalase-positive bacterial species.